An improved viscosity prediction model of extra heavy oil for high temperature and high pressure. (1st July 2022) - Jin, Fayang; Jiang, Tingting; Yuan, Chengdong; Varfolomeev, Mikhail A.; Wan, Fei; Zheng, Yufei; Li, Xiaowei
Graphical abstract: Highlights: An improved viscosity prediction model of extra heavy oil was built. Model is built based on Barus model and Chung model. Model is built based on filtration experiments. Model is suitable for viscosity prediction at high temperature and high pressure. Model can be used to predict viscosity of extra heavy oil. Abstract: Viscosity is an important parameter for the development and transportation of heavy and extra heavy oils, especially for those deep heavy oil reservoirs where oil is movable at reservoir temperature and pressure, but becomes unmovable when flowing to wellbore at some point with the decrease of temperature. It is very important to understand at which temperature and pressure heavy oil becomes unmovable. Most of the current viscosity prediction models for heavy oil mainly show the relationship between viscosity and temperature under atmospheric pressure. However, pressure also significantly affects the viscosity of heavy oil. In this work, extra heavy oil from Tahe oilfield was used to study the relation amongst viscosity, temperature, and pressure. According to the experimental data and their regression analysis, a new viscosity prediction model for extra heavy oil was proposed based on Barus model and Chung model. The new model is established on the basis of filtration experiments, which thus can more accurately reflect the real apparent viscosity when heavy oil flows in production pipeline. The model can be used to precisely predict the viscosity of extra heavy oil until 120 °C and 50 MPa (validated in this work) with the standard residuals of [−2, 2] and a high fitting degree (R 2 ) of close to 1, which can be employed for the different stages of reservoir development for numerical simulation, productivity evaluation, EOR treatments, as well as in-situ and ex-situ heavy oil upgrading processes.